Efektivitas Metode Debat Terhadap Kemampuan Berpikir Kreatif Siswa SMA - yeni suryaningsih; iim Halimatul Mu’minah (Papanda Journal of Mathematics and Science Research, 2022)
Education that helps development in the current era of globalization is education that is able to foster students' achievements, potential and abilities. In each stage of learning it is necessary to develop cognitive skills so that they can train students' creative thinking abilities. The purpose of this research is to develop the ability to think creatively through the debate method. The research method uses a true-experimental design and the instruments used are test questions with indicators of creative thinking ability and student activity observation sheets in learning using the debate method. The data collection technique was descriptive quantitative by testing the hypothesis using the nonparametric Two Independent Sample Test, namely the Mann-Whitney test and the gain score pretest-posttest The results showed that there was an increase in critical thinking skills in the experimental class with the highest N-Gain value of 0.39 (medium category) and in the control class only 0.26 (low category). The results of the hypothesis test obtained a significance value of 0.000 <0.005 and student activity in learning using the debate method obtained an average value of 70.70% in the good category. Based on the data analysis, it shows that the application of the debate method is very effective in helping students develop creative thinking skills.